Effect of oxygen partial pressure during preparation of rutile-type FeNbTiO6 on electrical and dielectric properties, thermopower and Mössbauer spectra. (May 2017) - Günther, A.; Hochleitner, R.; Lohringer, H.; Schmidbauer, E.; Schöttler-Himmel, A.; Volk, M.
Abstract: Electrical and dielectric properties were measured on rutile-type FeNbTiO6, sintered in air, CO2 or 5%H2 /CO2 atmosphere between temperatures of 1423 and 1573 K. The individual samples show characteristic differences in DC and AC conductivity, dielectric constant ε(ω) (ω is angular frequency), dielectric loss and dissipation factor. Attempts were made to distinguish between bulk, grain boundary (GB) and sample–electrode (SE) processes. Samples show very high relaxor-like ε(ω) peaks at 500−600 K using Ag-paint contacts as expected from previous studies during preparation in air that is of interest for industrial application; utilizing Pt-paint and using slightly reducing sintering conditions, a clear variation was observed. These findings point to a notable influence of GB and/or SE effects on the experimental ε(ω), in addition to the intrinsic origin by polar nanoregions, as suggested earlier. Complex plane impedance plots are characterized by semicircular arcs due to bulk, GB and/or SE charge transport. The derived DC conductivity σDC shows Arrhenius behavior with activation energy of E A ≈0.27–0.37 eV and σDC (300 K) ≈1×10 −6 –3×10 −4 Ω −1 cm −1 for the bulk, E A ≈0.7–0.9 eV and σDC (300 K)≈5×10 −10 –1×10 −4 Ω −1 cm −1 for GB and/or SE processes, depending on the preparation conditions. The thermopower is small and negative, hence n-type conduction occurs and the charge carriers are electrons or electron polarons. 57 Fe Mössbauer spectroscopy enabled to gain knowledge of local nonstoichiometry in the environment of Fe cations, presumably affecting electrical conduction in the bulk and GBs; after sample preparation in reducing conditions, apart from Fe 3+ also the presence of Fe 2+ ions was established. Highlights: Rutile-type FeNbTiO6 was synthesized in oxidizing and reducing atmosphere. Mössbauer spectra reveal Fe 3+ and Fe 2+ after preparation in reducing condition. Impedance spectra allow to distinguish between bulk and grain boundary conduction. Electrical DC and AC conductivities are higher after synthesis in reducing condition. Relaxor-type electrical constant is noted after preparation in both conditions.